Analysis of the influence of somatotype difference on motoric parameters such as vertical jump, sit and reach flexibility and 30-m sprint - Senol, Deniz; Ozbag, Davut; Kafkas, Muhammed E.; Acak, Mahmut; Baysal, Ozlem; Sahin Kafkas, Armagan; Ogeturk, Murat (Edizioni Minerva Medica, 2018)
BACKGROUND: The purpose of this study is to show the somatotype features of young people with no symptoms and to find out whether motoric parameters such as vertical jump, flexibility and 30-m sprint were influenced by somatotype differences. METHODS: The study included 146 participants (88 males, 58 females) who had no symptoms. The Heath-Carter formula was used to find out the somatotypes of the participants and each participant's anthropometric measurements were found. Vertical jump, flexibility and 30-meter sprint test were measured to evaluate motoric parameters of male and female. RESULTS: In men, athletes with central type somatotype had the best score in vertical jump test with 53 cm, athletes with endomorphic mesomorph somatotype had the best score in sit and reach flexibility test with 30 cm, and athletes with balanced mesomorph somatotype had the best score in 30-m sprint test with 4.36 s. In women, athletes with endomorphic mesomorph somatotype had the best score in vertical jump test with 40 cm, athletes with Endomorphic Mesomorph somatotype had the best score in sit and reach flexibility test with 33.5 cm, and athletes with mesomorph endomorph somatotype had the best score in 30-m sprint test with 5.22 s. No statistically significant difference was found in male and female between different somatotypes and motoric parameters (P>0.05). CONCLUSIONS: Although there were no statistically significant differences, it emerged that different somatotypes were more successful than others. An anatomic body structure specific for the sport branch influences performance greatly.
Analisi dell’influenza delle differenze somatotipiche su parametri motori come salto verticale, flessibilità sit-and-reach e sprint sui 30 metri
Keywords: Anthropometry; Somatotypes; Articular range of motion; Running; Athletic performance